Syntactic Comparison of Tagalog, Maori, and Chamorro - De Guzman, Videa (The Archive, 2023)
The search for language universals has brought out the relevance of describing a language not as though it were an isolated piece of structure, but rather as one that is related to other languages. Studies on the comparison of languages with view to discovering the properties which human languages share have contributed toward the formulation and/or evaluation of a general linguistic theory. Yet, the question as to what the characteristics of the "universal grammar" are is still unsettled and linguists agree that continued investigation or analysis of the world's languages may eventually yield the light. This paper is an attempt at positing some generalizations—some generalized syntactic relations, processes and features—which may be considered as candidates in the current thinking about the "universal grammar." The propositions are based on a comparison of some syntactic features in the basic sentence patterns of three genetically related languages, namely, Tagalog (T), Maori (M), and Chamorro (C).